Adoption of Malaysian good agricultural practices by vegetable farmers in Peninsular Malaysia - Rajendran, Natasha Ashvinee (2017)
Globally, sustainability standards have been promoted as a regulatory mechanism aimed at improving financial security, improving environmental quality and advocating labour equity. Good Agricultural Practices (GAP), one such standard, has been prevalently replicated by numerous governments to shape distinct national standards. Despite being heavily modelled after the successful international standard GlobalGAP, MyGAP, the Malaysian replica has experienced limited uptake since its genesis. The purpose of this research is to provide a focus on the MyGAP adoption process and the factors that influences the level of uptake. This thesis presents the three-objective outcome of a survey of 165 vegetable farmers conducted in several states in Peninsular Malaysia. Exploratory factor analysis revealed Compatibility, Complexity, Investment, Business returns and Trade Regulations to be focal attributes perceived by farmers, while a radar chart displayed Business Returns to be the most prominently perceived in terms of performance. Logistic regression revealed farming experience, formal education, gender, farm income) and membership in farmer group to be significant determinants of MyGAP adoption. Survival analysis was utilized to determine the adoption speed. Kaplan-Meier survival estimates revealed adoption to be rapid in earlier years, which then declined as time progressed. Cox regression revealed labour availability to be an adoption speed accelerator, while income, farm-market distance and technical assistance from change agents to reduce the speed. The overall findings suggest multidisciplinary policy implications aimed at improving a farmer’s capacity to procure knowledge and manage risks (monetary and non-monetary). Policy implications include encouraging a decentralized, flexible learning experience between change agents and farmers. Modernizing information diffusion tools and enhancing economic opportunities to help encourage and retain adoption among local vegetable farmers. It is hoped that the implications generated by the findings of this thesis will serve as an instrumental policy change to guide the Malaysian Ministry of Agriculture in improving their extension services, thus helping farmers improving a farmer’s capacity to procure knowledge and manage risks (creating markets for MyGAP produce, enabling premium payments).